Homophily among VAA users: Similarities and differences of node attributes in a VAA-generated social network - Manavopoulos, Vasilis (My University, 2014)
Users who successfully invited others to the EUvox 2014 online platform and users who accepted the invitation were used to form a network dataset. This report examines the tendency of Inviters and Invitees to be disproportionately similar with respect to their demographic, political orientation and attitudinal characteristics, i.e. Examines the homophily hypothesis in VAA generated data. We find that Inviters were not more similar to their respective Invitees with regards to demographic and political identity attributes, beyond what would be expected by chance, on the contrary we find that the pairs held consistency more similar attitudes toward the policy items in a statistically significant manner.
Keywords: Homophily; Social Network Analysis; VAA